THE ORAL TRADITION OF UNTUNG SUROPATI AMONG THE PEOPLE OF PASURUAN FROM 1975 TO 2018 - Diah Ayu Octavia; sumarjono sumarjono; marjono marjono (JURNAL HISTORICA, 2020)
The oral tradition of Untung Suropati is message or stories about Untung Suropati that aretold from generation to generation oral. The oral tradition does not include eye witnesswhich is oral data, but is transmitted from one generation to another. Function of oraltradition of Untung Suropati value is a projection system or reflection and as aneducational amenity. The results of the research obtained are contextual backgrouds of theoral tradition in the form of recitations that have been exitedfor a long time, posibly sincethe death of Untung Suropati. The oral tradition in the form of procession Kirab Pataka waexamined by a team established by Hari Jadi Kota Pasuuan cooperated with DinasPendidikan dan Kebudayaan Kota Pasuruan in 2002. The oral tradition in the form ofdance drama (dramatari) introduced by art studios of Dharma Budaya. Embodiment ofUntung Suropati story in each of the oral tradition obtains a different story. Historicalvalue in the oral tradition which can be engaged as a historical source is the form ofprocession Kirab Pataka.